Channel Length-Based Comparative Analysis of Temperature and Electrical Characteristics for SiNWT and GeNWT - AlAriqi, Hani Taha; Jabbar, Waheb A.; Hashim, Yasir; Hadi, Manap (University of Bahrain, 2020)
This paper investigates the temperature sensitivity and electrical characteristics of Silicon Nanowire Transistor (SiNWT) and Germanium Nanowire Transistor (GeNWT) depending on variable channel length (Lg). It also studies the possibility of using them as a temperature nanosensor. The MuGFET simulation tool was exploited to investigate the characteristics of the considered nanowire transistors. Current-voltage characteristics with different values of temperature with channel length [Lg = 25, 45, 65, 85 and 105 nanometer (nm)], were simulated. MOS diode mode connection suggested measuring the temperature sensitivity of SiNWT and GeNWT too. Three (3) electrical characteristics namely; (i) Subthreshold Swing (SS), (ii) Threshold voltage (VT), and (iii) Drain-induced barrier lowering (DIBL) were evaluated and compared for both NWTs. The obtained results show that SiNWT achieved a better temperature sensitivity with channel length range between 25 nm to 105 nm at operation voltage (VDD) range 1 V to 5 V nm. It is very clear that the temperature sensitivity increased remarkably by increasing channel length for both of SiNWT and GeNWT as well, but in SiNWT the sensitivity is more steady compared to GeNWT that showing less sensitivity. Moreover, SiNWT shows better result in terms of electrical performance metrics for various channel length at T = 300 K comparing with GeNWT.